The unconscious: a bibliographical and comparative review of different views on the concept - Hinojosa, Adrián (2016)
Currently, in the academic field, the different currents in psychology are often opposed without deepening their points of agreement. As a result of this, the present investigation makes a comparison of the unconscious concept according to: Sigmund Freud father of Psychoanalysis; Milton Erickson influencing the Systemic model; And Manuel Froufe compiler and impeller of the unconscious within the Cognitive model. The methodology was documentary, for which we used texts extracted from specific search engines such as: Google Academic, Redalyc, Scielo, Proquest, and books of authors relevant to the topic. It was concluded that there is a difference in the area in which the term was developed, being clinical in Erickson and Freud and academic-experimental in Froufe. It is also important to note that the popularity of the unconscious is remarkable in Freud, in Erickson's case it is comparatively minor, but not so with the cognitive unconscious, because its formulation is of recent appearance and does not yet have clinical developments.